Relationship between academic procrastination and attributions of achievement motivation - Quispe-Bendezú, L.E. (2020)
The research aims to determine the relationship between the tendency to academic procrastination and the motivational attributions of achievement in students of the seventh cycle of the EBR of the province of Arequipa. The research is divided into two, first the adaptation and validation of the General Achievement Attribution Motivation Scale (EAML-G) of Durán-Aponte and Pujol (2013) to a secondary level student population, for this, the data are collected from a sample of 72 students, of which 35 were women and 37 men between 15 and 17 years old; the items for the new population were modified; The results show that the adapted General Achievement Motivation Scale (EAML-G) is valid and reliable to identify the causal attributions of general performance in secondary level students. The second research was focused on determining the relationship itself, for this the analysis was made in a representative sample of 677 students, aged between 14 and 19 years, with an average of 15.78 years, of which 476 were male and 201 women, it was found that procrastination is inversely related to the attributions to the interest, capacity, characteristics of the task and teacher evaluation, likewise, the relationship between Academic Procrastination and age is fragile.